Perineal groove: a rare anogenital anomaly. - Tambe, S.; Kernland Lang, K.; Saple, D.G. (European Journal of Pediatric Dermatology, 2015)
The perineal groove is a rare and usually uncomplicated congenital malformation of the perineum characterized by a wet sulcus – because covered by non keratinizing epithelium – that extends from the posterior fourchette to the anus. It has been very rarely described in dermatology literature. Here we report a case of this uncommon entity in a 6-year-old female child.